Evaluasi Model Kirkpatrick terhadap Program Khusus Dai pada Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari - Huda, Nuril; Dahliana, Difi; Aseri, Akh Fauzi (el Buhuth: Borneo Journal of Islamic Studies, 2022)
Evaluation is very important for a program.model for assessing a program is the Kirkpatrick model which consists of the reaction level, learning level, behavior level, and final outcome level. This evaluation model is one of the most popular educational evaluation models around the world, and has been widely used to evaluate training programs in various countries. However, this model has never been used to evaluate Dai's Special Program at the Faculty of Da'wah and Communication Sciences, Antasari State Islamic University, Banjarmasin, so the results are not yet known. Therefore, the authors are interested in conducting an evaluation study of the Dai Special Program based on the Kirkpatrick evaluation model. The results of this mixed methods research show that the Dai Special Program at the Faculty of Da'wah and Communication Sciences, Antasari State Islamic University Banjarmasin at the reaction level, learning level, and behavior level has been implemented well. However, the results of the evaluation at the final outcome level show that this program still needs improvement because the results of this program have not shown optimal results.